Pertumbuhan dan Hasil Kacang Hijau (Phaseolus radiatus L.) dengan Pemberian Air Kelapa - rufino wijaya; Alvera Prihatini; Syamad Ramayana (Jurnal Agroekoteknologi Tropika Lembab, 2019)
Coconut water can increase the growth and yield of plants because itcontains plant growth regulator (PGR): auxin, cytokinin and gibberellin, vitamin, and mineral.The research was carried out to know: 1) the effect of coconut water concentrations on the growth and yield of mungbean and 2) concentration of coconut water that provide the best growth and yield of mungbean. The experiment was conducted during three months, from September until November 2017, located in Samarinda.The experiment was arranged in Completely Randomized Design (CRD) wasa single factor experiment, concentration of coconut water, consisted of four treatments: 0; 20; 40; and 60% of coconut water and each treatment was replicated six times. The data were analyzed by analysis of variance (anova) and continued by Least Significant Difference (LSD) test at significantlevel of 5%.Variables that observed were plant height, number of branches, number of pods, number of seeds, number of unfilled pods, weight of filled pods, andweight of seedsper plant.The result showed that the effect of coconut water concentrations was highly significant on plant height at 4, 6 weeks and at harvest time, number of pods, number of seeds, weight of filled pods, and weight of seeds per plant,howeveritwas significantly different on plant height at 2 weeks and number of branches, and it was no significantly different on number of unfilled pods. The best growth and yield of mungbean obtained by concentration 40% of coconut water.